Classification of Human–Elephants Conflict Mitigation Systems in Bukit Barisan Selatan Conservation Area from a Multispecies Perspective for the Protection of Protected Wildlife - Basyarul Aziz; Cindi Adelia Putri Emas; Khoirun Nisa Aulia Sukmani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
Human–wildlife conflict in Bukit Barisan Selatan National Park (BBSNP), particularly in Pekon Pemerihan, has intensified due to deforestation, land-use change, and expanding agriculture, threatening endangered species such as the Sumatran elephant (Elephas maximus sumatranus). This study formulates the problem of how local communities classify and mitigate conflicts with elephants through ethnoecological knowledge, and how such knowledge can be integrated with a multispecies perspective for sustainable coexistence. Using qualitative methods, data were collected through field observations, in-depth interviews with farmers and mahouts, and participatory mapping. The findings reveal a three-level classification system: (1) domains distinguishing wild and managed elephants and safe versus risk-prone spaces; (2) taxonomies of conflict types (economic, social, spiritual) and elephant identities; and (3) components involving technical, social, temporal, and ritual strategies. Results show that conflicts are understood not only ecologically but also cosmologically, with elephants seen as moral agents shaping human life. The study concludes that effective mitigation must integrate technical interventions with local ecological knowledge, cultural values, and community solidarity to achieve more adaptive and just conservation strategies.